Consumption that matters - Andersen, Sophie Esmann; Stage, Carsten (MedieKultur: Journal of media and communication research, 2010)
The purpose of this article is to contribute to the understanding of a rising mode of ethical consumption by exploring the brand concept (RED) and its intertwinement of commerce and charity. Based on an analysis of central online media texts, we focus on: 1) the campaign’s “cool” visual and verbal structures of appeal, and 2) the discursive struggle concerning the ethical potential of consumption motivated by the campaign. The analysis is followed by a discussion of the potential and problems of (RED) as a way of handling global responsibility for distant suffering others. We argue that from a perspective focusing on the representation of the distant sufferer, (RED) can be criticised for transforming suffering into aesthetic spectacles in order to legitimise hedonistic consumption. The potential of the campaign is that it acknowledges that effective ethical ways of relating to distant others will have to be integrated into the narratives of self and community circulating in a given context.